PENGARUH PEMBERIAN TEPUNG SAGU (Metroxylon SP) TERHADAP PERFORMANS TERNAK BABI RAS FASE GROWER - ., suparman (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Sains dan Teknologi Jayapura, 2021)
This study aims to determine the effect of adding sago flour (Metroxylon SP) in commercial rations on the performance of pigs in the grower phase. This study used an experimental method using a completely randomized design (CRD), which consisted of 4 treatments and 3 replications so as to obtain 12 experimental units. The research treatments were: R0 (commercial ration CP551 as control diet), R1 (95% commercial ration CP551 + 5% sago flour), R2 (90% commercial ration CP551 + 10% sago flour) and R3 (85% commercial ration CP551 + 15% sago flour). This study used 12 pigs, aged 3 months with an initial body weight range of 9.9 to 10.36 kg. Research feed was given for 6 weeks. The variables measured included average body weight gain (PBB), ration consumption, ration conversion. The results showed that the provision of sago flour in commercial rations on body weight gain (0.908-1.083 kg/head/day), total consumption (2.075-2.083 kg/head/day) and ration conversion (1.944-2.287 kg/head/day) did not significant effect (P>0.05). The use of sago flour in commercial rations for pigs in the grower phase can provide good growth even though body weight gain, total consumption and ration conversion remain the same. Keywords: Grower Phase, Performance, Sago Flour